Peran Guru terhadap Motivasi Belajar Siswa di SMK Al-Fudhola’ Sungai Lilin - Karimah, Ummul; Nasution, Nasution; Purwandari, Elce (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the role of teachers in motivating students, identify factors that influence low motivation, analyze the forms of teacher-student interactions that impact motivation, and uncover the obstacles that teachers face in their role as motivators of learning. The research method employed was a descriptive qualitative approach with purposive sampling. The results indicate that teachers play a strategic role in fostering student learning motivation through a personalized approach, utilizing varied methods such as educational games and awarding points, as well as providing individual attention. Factors influencing low motivation include low interest in learning, lack of support from the school environment, and negative influences from the external environment. In conclusion, the role of teachers at SMK Al-Fudhola' Sungai Lilin is crucial in building student learning motivation. Teachers act not only as instructors but also as motivators, capable of arousing interest, fostering positive attitudes toward learning, and fostering student self-confidence. Keywords: Learning Motivation, Teacher Role, SMK Al-Fudhola'